Pendekatan Proses Sains Menggunakan Metode Eksperimen Bebas Termodifikasi dan Eksperimen Terbimbing untuk Peningkatan Hasil Belajar Dan Kreativitas Belajar - Ritonga, Megawati; Darmana, Ayi; Rahayu, Ucu (Mahesa Research Center, 2021)
This study aims to determine the relationship between learning outcomes with student learning creativity. This research was carried out in SD Negeri 118401 Pinang Awan in the odd semester of the 2019/2020 school year. The population is all students of class IV as many as 70 students consisting of 2 classes, class A and class B which are 35 students each. All populations are sampled. Class A as an experimental class one and class B experimental class two. The instruments used were tests and learning motivation questionnaires. The test instruments consisted of 11 items multiple choices and 42 items in the questionnaire. The study used a quasi-quasi-experimental method (Quasi Experiment Design). Data analysis techniques used the t-test at a significant level É‘ = 0.05.The results of the research analysis is a relationship between learning outcomes with student learning creativity seen from Sig. (2-tailed) 0.011 <0.05. The conclusion that students use the modified free experimental method is better than the science learning outcomes of students using the guided experimental method. Whereas the creativity that is taught using the modified free method and the guided experimental method is low.